Primary school buildings in the Lublin area designed by the architect Bohdan Kelles‑Krauze during the interbellum period - Miłkowska, Ewa (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2023)
A general lack of primary school buildings at the start of the Second Polish Republic encouraged architects of that period to take action. However, strict ministerial criteria concerning the functional and spatial layout of school buildings, as well as lack of consistent construction law in the reborn Poland made it impossible to introduce original solutions to both school buildings and their surroundings. Pattern books published by the Ministry of Religious Beliefs and Public Enlightenment were commonly used. Within the Lublin School District, as many as nine school buildings were designed by Bohdan Kelles-Krauze. Although original projects, they complied with the general regulations applicable for this type of buildings.